Exploring the Place of Values in the New Social Work Degree in Scotland. - Mackay, Kathryn; Woodward, Rona (Social Work Education, 2010)
Social work education in the UK has experienced major changes in recent years with the move to an honours degree qualification. Introduced in 2003, the new degree requires students to develop skills in analysis and critical reflection yet, almost six years later, it would appear that this level of critical analysis is not being demonstrated consistently in relation to values. Two weak areas standout: understanding service users' situations at a structural level, and recognising the importance of anti-oppressive practice. This paper draws upon UK literature, and the authors' own experiences to date, to explore why the new degree seems to fall short when it comes to the development of a strong values framework in students. In particular, it is argued that increased standardisation in social work education, as well as practice, is one possible explanation. Focusing on the Scottish situation, it is suggested that standardisation has become even more apparent since the introduction of new Key Capabilities in Child Care and Protection in 2006, which students are now required to meet in addition to the existing Scottish Standards in Social Work Education.